CHRONIC CERVICITIS AND HPV-INFECTION IN REPRODUCTIVE PERIOD. ROUTS TO DECREASE DIAGNOSTIC AND TREATMENT AGRESSION - T. S. Kachalina; N. M. Shakhova; O. V. Kachalina; D. D. Eliseyeva (Акушерство, гинекология и репродукция, 2016)
In present work urgency of the problem of HPV-associated cervical disease in reproductive age is justified. While monitoring 170 patients new approaches of improvement of cervical cancer secondary prevention methodswere proposed. These methods optimize non-invasive diagnostics of HPV-related precancerous cervicitis as its early indicators. Taking into account increase in incidence of cervical cancer in reproductive age, various tactics of patients with human papilloma virus infection (HPV) follow up based on complementary usage of traditional methods and new optical technologies - optical coherence tomography (OCT) in the diagnostic phase and photodynamic therapy (PDT) as a treatment method were considered. We justify the expediency of treatment withPolygynaxsuppository at different therapy stages of patients with chronic HPVand use of new modification of OCT (speed imaging 8-10 frames per second), which allows to determine the size of the tank and the main foci of infection that maximally eliminates random biopsy and allows to assess surface of eсtocervixafter treatment in dynamics. The authors suppose that the use of the proposed tactics in chronic cervicitis associated with HPV, will optimize the diagnostic process by eliminating unjustified cervical trauma, as well as to justify sparing therapeutic effect in women of reproductive age